Correlation of ultrasonographic estimated fetal weight with actual birth weight at a rural setting - Hashim, Elnazeer A.; Saeed, Elsir A.; Mohamed, Elsadig Y.; Ebaid, Elabbas M.; Zain, Hussam; Abdalla, Sawsan M.; Medani, Khalid E.; Albarakati, Rayan G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Ultrasound estimation of fetal weight in term pregnancies is used to determine fetal growth. The objective of this study was to assess the precision of sonographic estimation of fetal weight in normal vaginal deliveries at a rural setting. Methods: The study was cross-sectional. A group of 74 pregnant women delivered normally in Muglad hospital in West Kordofan, Sudan, were considered in the study. Fetal weight was estimated by Hadlock and shephards formulae within one week prior to delivery and then newborn weight was taken within 24 hours after delivery. Data were collected by a questionnaire and medical examination as well as sonographic examination. Data analysis was done by SPSS version 23 and Kruskal Wallis Test (post-hoc analysis) Pearson’s correlation coefficient within 95% confidence interval. p value <0.05 was considered as statistically significant. Results: The correlation, by Paired sample, to assess fetal weight was as follows: between Hadlock and shephards was 0.901 (p < 0.001), between Hadlock and AFW was 0.908 (p < 0.001) and between Shephards and AFW was 0.781 (p < 0.001). Conclusions: Estimation of fetal weight by Hadlock has been more correlated with actual fetal weight (AFW) than that done with shephards. The study recommends using Hadlock formula which is more accurate in estimation of fetal weight by sonography.